Increases in statin eligibility to reduce cardiovascular risk according to the 2013 ACC/AHA cholesterol guidelines in the Africa Middle East region: a sub-analysis of the Africa Middle East Cardiovascular Epidemiological (ACE) study - Raal, Frederick J.; Hamoui, Omar; Omar, Mohamed I.; Rashed, Wafa; Kane, Abdoul; Alami, Mohamed; Abreu, Paula; Mashhoud, Walid; Alsheikh-Ali, Alawi A. (BioMed Central, 2019)
Background: With development of cholesterol management guidelines by the American College of Cardiology/ American Heart Association (ACC/AHA), more individuals at risk of cardiovascular disease may be eligible for statin therapy. It is not known how this affects statin eligibility in the Africa and Middle East Region. Methods: Data were used from the Africa Middle East Cardiovascular Epidemiological (ACE) study. The percentage of subjects eligible for statins per the ACC/AHA 2013 cholesterol guidelines and the 2002 National Cholesterol Education Program-Adult Treatment Panel (NCEP-ATP III) recommendations were compared. Analyses were carried out according to age, gender, community (urban/rural), and country income categories based on World Bank definitions. Results: According to the ACC/AHA recommendations, 1695 out of 4378 subjects (39%; 95% confidence interval [CI], 37–40%) satisfied statin eligibility criteria vs. 1043/4378 (24%; 95% CI, 23–25%) per NCEP-ATP recommendations, representing a 63% increase in statin eligibility. Consistent increases in eligibility for statin therapy were seen according to the ACC/AHA vs. NCEP-ATP guidelines across sub-groups of age, gender, community, and country income. Notable increases for statin eligibility according to ACC/AHA vs. NCEP-ATP were seen, respectively, in subjects aged ≥65 years (86% vs. 39%), in males (46% vs. 25%), in low-income countries (28% vs. 14%), and rural communities (37% vs. 19%). Conclusion: An increase in statin eligibility was seen applying ACC/AHA cholesterol guidelines compared with previous NCEP-ATP recommendations in the Africa Middle East region. The economic consequences of these guideline recommendations will need further research.
Keywords: Africa Middle East region; Cholesterol guidelines; Lipid-lowering therapy; Income; The Africa and Middle East Cardiovascular Epidemiological (ACE) study; Statin therapy; SDG-3: Good health and well-being